Wadden Sea Eutrophication: Long-Term Trends and Regional Differences - van Beusekom, Justus E. E.; Carstensen, Jacob; Dolch, Tobias; Grage, Annika; Hofmeister, Richard; Lenhart, Hermann; Kerimoglu, Onur; Kolbe, Kerstin; Pätsch, Johannes; Rick, Johannes; Rönn, Lena; Ruiter, Hans (Frontiers in Marine Science, 2019)
The Wadden Sea is a shallow intertidal coastal sea, largely protected by barrier islands and fringing the North Sea coasts of The Netherlands, Germany and Denmark. It is subject to influences from both the North Sea and major European rivers. Nutrient enrichment from these rivers since the 1950s has impacted the Wadden Sea ecology including loss of seagrass, increased phytoplankton blooms and increased green macroalgae blooms. Rivers are the major source of nutrients causing Wadden Sea eutrophication. The nutrient input of the major rivers impacting the Wadden Sea reached a maximum during the 1980s and decreased at an average pace of about 2.5 % per year for total Nitrogen (TN) and about 5 % per year for total Phosphorus (TP), leading to decreasing nutrient levels but also increasing N/P ratios. During the past decade, the lowest nutrient inputs since 1977 were observed but these declining trends are levelling out for TP. Phytoplankton biomass (measured as chlorophyll a) in the Wadden Sea has decreased since the 1980s and presently reached a comparatively low level. In tidal inlet stations with a long-term monitoring, summer phytoplankton levels correlate with riverine TN and TP loads but stations located closer to the coast behave in a more complex manner. Regional differences are observed, with highest chlorophyll a levels in the southern Wadden Sea and lowest levels in the northern Wadden Sea. Model data support the hypothesis that the higher eutrophication levels in the southern Wadden Sea are linked to a more intense coastward accumulation of organic matter produced in the North Sea.